’If Ya Wanna End War and Stuff, You Gotta Sing Loud’ -A Survey of the Provisional Agreement between FARC and Colombia on Illicit Drugs - Seatzu, Francesco (Araucaria, 2016)
Although still neglected in legal writings, the 2014 agreement on illicit drugs between the FARC and the Colombian Government deserves attention for a number of reasons, including that it was conceived as an essential part of the broader strategy for peace in Colombia, as well as because of its aim of eradicating illicit crops. Starting with some remarks on the Colombian ’drug war’ and the policy and legal arguments for classifying the Colombian armed conflict as a non-international armed conflict (NIAC), the paper will then proceed with an analysis of the main reasons behind the drafting of a partial agreement on illicit drugs between the FARC and Colombia in 2014. Next, the paper will address the relevant sections and enforcement mechanisms for putting the provisions of the agreement into effect. An assessment of how the 2014 agreement has addressed the issue of drug trafficking and the issues concerning drug related crimes will also be considered. The paper will conclude with the lessons to be drawn from the new Agreement on illicit drugs.